Elements of environmental management - Antweiler, Werner (University of Toronto Press, 2014)
As businesses face an increasing array of environmental challenges, including climate change, air and water pollution, and solid waste management, environmental management has become an increasingly important area of expertise. Elements of Environmental Management is an interdisciplinary textbook for students and business professionals that integrates corporate environmental strategy with environmental economics, environmental law, and environmental engineering.- Resumé vydavatel
Keywords: environmentální management; podnikový management -- environmentální aspekty; environmentální strategie; environmentální ekonomie; environmental management; industrial management -- environmental aspects; environmental strategy; environmental economics; elektronické knihy; učebnice vysokých škol; electronic books; textbooks (higher)